Analisis Manajemen Risiko TI Menggunakan COBIT 5 Domain APO12 pada PT VWX - Sanjaya, Aloisius Egi; Wikananda, Ketut Agus; Sitompul , Mayer Dhani; Andayani , Sri (CV. Information Technology Training Center - Indonesia (ITTC), 2026)
The use of Information Technology (IT) in distribution companies plays a crucial role in supporting operational efficiency, data accuracy, and business continuity. PT VWX is a stationery (ATK) distribution company that procures goods from factories and distributes them to suppliers in large quantities. The company relies on a centralized application provided by the head office and utilizes Microsoft Excel for data input processes. This dependency creates several IT-related risks, including human error in data entry, dependency on centralized systems, limited IT human resources, and outdated hardware specifications. This study aims to analyze IT risk management at PT VWX using the COBIT 5 framework, specifically the APO12 (Manage Risk) domain. The research method involved interviews with IT personnel and an analysis of the As-Is and To-Be conditions. The results indicate that the current IT risk management capability level is at Level 2 (Managed Process), which has not yet reached the targeted Level 3 (Established Process). Therefore, formal procedures, risk registers, and improved risk mitigation mechanisms are required to achieve more systematic and proactive IT risk management.